Substantiation of estimated indicators of rural development and rural population reproduction - Pavlova Kseniya; Ilyina Larisa (BIO Web of Conferences)
Rural development is necessary to increase the economic independence of the country. Without labor resources and a high quality of life in rural areas, it is impossible to ensure food security. Government support plays an important role for the reproduction of the rural population, nevertheless, statistical data indicate the persistence of a number of problematic areas in rural development. There are many approaches for assessing the effectiveness of rural development, allowing to see both problematic and successful areas to adjust measures to improve the standard of living in rural areas. The author’s approach provides for a wide range of indicators - indicators of rural development and reproduction. The indicators of rural development and rural population reproduction presented in the study consider not only quantitative indicators based on statistical estimates, but also qualitative indicators based on rural satisfaction assessments and considering specific qualitative changes in parameters characteristic of rural areas obtained through social surveys, focus group work, and expert assessment analysis. The authors propose a methodology for assessing rural development and reproduction indicators based on the calculation of weighted averages for a specific territory. This approach allows to rank data and compare data across different regions, for example, within federal districts, to create a regional rating. The rating will allow potential rural residents to choose a comfortable area to live in, government agencies to adjust the goals and methods of financial and administrative support, investors and agricultural enterprises to consider the socio-economic potential of the region in adopting business strategies.